Effects of Ti-substitution on the crystal structures, micro-structures and microwave dielectric properties of Li2Mg3Zr1-xTixO6 (0 ≤ x ≤ 1) ceramics. Issue 5 (1st April 2018) - Yang, C.H.; Pan, H.L.; Yang, Y.K.; Wu, H.T.
Abstract: Li2 Mg3 Zr1−x Tix O6 (x = 0, 0.2, 0.4, 0.6, 0.8, 1) ceramics were prepared via a solid-state reaction method. Crystal structures, sintering behaviors, micro-structures and microwave dielectric properties of Li2 Mg3 Zr1−x Tix O6 (0 ≤ x ≤ 1) ceramics were investigated by XRD, SEM and chemical bond theory. XRD results showed that a single phase with the rock-salt structure was formed in all ranges. On the basis of the Rietveld refinement and chemical bond theory, several intrinsic parameters were calculated and connections between intrinsic parameters and microwave dielectric properties were investigated. The substitutions of Ti 4+ for Zr 4+ obviously increased the relative density and improved the quality factors. Variations of ε r could be explained by changes of the polarizability. Q·f values showed the similar trend with the packing fractions, average bond valences and lattice energy of Zr–O bonds. τ ƒ values significantly correlated with the bond energy of Zr–O bonds.